Not Only COVID-19: Involvement of Multiple Chemosensory Systems in Human Diseases - Caretta, Antonio; Mucignat-Caretta, Carla (Frontiers in Neural Circuits, 2022)
Chemosensory systems are deemed marginal in human pathology. In appraising their role, we aim at suggesting a paradigm shift based on the available clinical and experimental data that will be discussed. Taste and olfaction are polymodal sensory systems, providing inputs to many brain structures that regulate crucial visceral functions, including metabolism but also endocrine, cardiovascular, respiratory, and immune systems. Moreover, other visceral chemosensory systems monitor different essential chemical parameters of “milieu intérieur,” transmitting their data to the brain areas receiving taste and olfactory inputs; hence, they participate in regulating the same vital functions. These chemosensory cells share many molecular features with olfactory or taste receptor cells, thus they may be affected by the same pathological events. In most COVID-19 patients, taste and olfaction are disturbed. This may represent only a small portion of a broadly diffuse chemosensory incapacitation. Indeed, many COVID-19 peculiar symptoms may be explained by the impairment of visceral chemosensory systems, for example, silent hypoxia, diarrhea, and the “cytokine storm”. Dysregulation of chemosensory systems may underlie the much higher mortality rate of COVID-19 Acute Respiratory Distress Syndrome (ARDS) compared to ARDSs of different origins. In chronic non-infectious diseases like hypertension, diabetes, or cancer, the impairment of taste and/or olfaction has been consistently reported. This may signal diffuse chemosensory failure, possibly worsening the prognosis of these patients. Incapacitation of one or few chemosensory systems has negligible effects on survival under ordinary life conditions but, under stress, like metabolic imbalance or COVID-19 pneumonia, the impairment of multiple chemosensory systems may lead to dire consequences during the course of the disease.